Rare earth magnet, method for manufacturing the same and motor having the same
By diffusion treatment of double-sided C-plane rare earth elements on NdFeB rare earth magnets and limited polishing, the problem of insufficient thermal resistance of rare earth magnets in electric vehicle motors is solved, and the dimensional accuracy and high coercivity of the magnet are achieved.
Patent Information
- Application Number
- JP2023152042
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
Rare earth magnets used in electric vehicle motors have insufficient quality in terms of thermal resistance, which leads to diffusing rare earth elements from the magnet surface, reducing coercivity, and inaccurate magnet size during polishing, affecting the performance of the final product.
The double-sided C-plane rare earth element diffusion treatment is performed on the NdFeB rare earth magnet and a limited polishing treatment after diffusion is performed to ensure the dimensional accuracy and high coercivity of the magnet.
The rare earth magnets have excellent magnetic properties in electric vehicle motors, while ensuring the dimensional accuracy and high coercivity of the magnets, avoiding performance degradation caused by polishing.
Smart Images

Figure 2025044468000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a rare earth magnet, a manufacturing method thereof, and a motor equipped with the same. [Background technology]
[0002] In recent years, Sm-Co rare earth magnets and RTB permanent magnets, such as Nd-Fe-B rare earth magnets, have been put to practical use as high performance rare earth magnets.
[0003] For example, Patent Document 1 discloses a method for producing an R-Fe-B sintered magnet, which comprises: 1) producing an R-Fe-B sintered magnet by a known method; 2) subjecting the sintered magnet to degreasing, pickling, activation, and cleaning treatments with deionized water; 3) preparing a uniform slurry of ultrafine terbium powder, an organic solvent, and an antioxidant, and covering the surface of the sintered magnet treated in 2); and 4) sintering and aging the magnet in 3).
[0004] Patent Document 2 discloses a sintered magnet that includes particles having a main phase mainly composed of a compound containing rare earth elements and iron, and a diffusion layer provided on the surface of the main phase, the diffusion layer mainly composed of a compound in which at least one of carbon and nitrogen is dissolved in the compound of the main phase, and the at least one of the carbon and the nitrogen has a concentration gradient from the surface to the inside of the particle.
[0005] Patent Document 3 describes a sintered magnet body that contains a specific element R, expressed as atomic percent, in at least a portion of the surface vicinity of the main phase particles within at least 500 μm from the surface of the sintered magnet body. 2 A layer 1 having a higher concentration than the center of the particle, and a layer 2 having a higher concentration than the layer 1. 2 A layer 2 having a lower concentration, and a layer 3 having a lower concentration than the layer 2. 2 The present invention discloses an R-Fe-B based sintered magnet characterized by the presence of multi-layered main phase grains having multiple layers including a layer 3 with a high concentration. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2018-82145 A [Patent Document 2] JP 2020-21804 A [Patent Document 3] JP 2020-57734 A Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, the heat resistance quality of motors used in electric vehicles and the like is ensured by diffusing rare earth elements from the magnet surface in the motor to increase the coercivity and reduce the heavy rare earth elements. Generally, the magnet obtained expands after the rare earth elements are diffused, so the magnet must be polished to ensure the final magnet dimensions, and a resin coating must be formed or a coating must be formed by plating or the like.
[0008] However, the inventors have found that when a magnet, particularly a sintered magnet, is polished, the magnet surface contains exposed main phase that is not surrounded by the grain boundary phase rich in rare earth elements. The particles in the main phase can cause the magnet to lose its performance, particularly its coercive force (Hc), and can cause demagnetization in low magnetic fields. As a result, the magnet obtained can suffer from reduced coercive force and reduced residual magnetization (knicks).
[0009] SUMMARY OF THE PRESENT EMBODIMENTS An object of the present invention is to provide an RTB rare earth magnet that ensures dimensional accuracy and at the same time has excellent magnetic properties. [Means for solving the problem]
[0010] The present inventors have studied various means for solving the above problems, and have found that in an NdFeB rare earth magnet in which grain boundary diffusion has occurred from both C faces, by performing limited polishing after grain boundary diffusion, it is possible to ensure the dimensional accuracy of the obtained NdFeB rare earth magnet when it is inserted into a rotor, and at the same time, to maintain the coercive force, and thus completed the present invention.
[0011] That is, the gist of the present invention is as follows. (1) An RTB rare earth magnet in which R is a rare earth element, T is iron (Fe) and / or cobalt (Co), and B is boron, the RTB rare earth magnet having a magnet region layer and a surface layer covering the C-face of the magnet region layer, the magnet region layer being R2T 14 The RTB rare earth magnet comprises a main phase having a B-type crystal structure and a grain boundary phase existing around the main phase, the main phase having an average grain size of 1.0 μm to 10.0 μm, and the surface layer covering 85% or more of the C-face of the magnet region layer relative to the total area of the C-face. (2) The RTB rare earth magnet according to (1), wherein the main phase has a core portion and a shell portion surrounding the core portion, and the total content of neodymium (Nd), praseodymium (Pr), terbium (Tb), dysprosium (Dy), and holmium (Ho) in the shell portion relative to all of the constituent elements of the shell portion is higher than the total content of Nd, Pr, Tb, Dy, and Ho in the core portion relative to all of the constituent elements of the core portion. (3) The composition of the surface layer and the grain boundary phase is represented by the formula: R 2 (1-s) M 2 s (In the formula, R 2 is one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, cerium (Ce), lanthanum (La) and Ho, M 2 is R 2 and (1-s) and (s) are metal elements other than rare earth elements that are alloyed with the rare earth elements, and unavoidable impurity elements, and (1-s) and s are molar ratios, and 0.05≦s≦0.40. (4) The RTB rare earth magnet according to any one of (1) to (3), wherein the rare earth concentration in the surface layer is higher than the rare earth concentration in the magnet region layer. (5) A motor including a stator core having a coil, and a rotor core rotatably disposed in a hollow portion of the stator core, the rotor core including an RTB rare earth magnet according to any one of (1) to (4). (6) A method for producing an RTB rare earth magnet, in which R is a rare earth element, T is Fe and / or Co, and B is boron, comprising: a first step of diffusing and infiltrating a rare earth magnet precursor with a diffusing material to prepare a diffusion material-infiltrated rare earth magnet precursor having a magnet region layer and a surface layer covering a C-face of the magnet region layer; and a second step of polishing the diffusion material-infiltrated rare earth magnet precursor to produce an RTB rare earth magnet, wherein in the first step, the diffusing material is an element represented by the formula: R 2 (1-s) M 2 s (In the formula, R 2 is one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, Ce, La and Ho, and M 2 is R 2 and the rare earth element and the metal element and the inevitable impurity element which are alloyed with the rare earth element, and (1-s) and s are molar ratios, and 0.05≦s≦0.40. 14 the method comprising: a main phase having a B-type crystal structure; and a grain boundary phase surrounding the main phase, the main phase having an average grain size of 1.0 μm to 10.0 μm; and in a second step, polishing is performed such that a surface layer present on a C-face of the diffusion material-permeated rare earth magnet precursor remains at 85% or more of the total area of the C-face of the diffusion material-permeated rare earth magnet precursor. (7) A method for producing an RTB rare earth magnet, in which R is a rare earth element, T is Fe and / or Co, and B is boron, comprising: a first step of diffusing and infiltrating a rare earth magnet precursor with a diffusing material to prepare a diffusion material-infiltrated rare earth magnet precursor having a magnet region layer and a surface layer covering a C-face of the magnet region layer; and a second step of polishing the diffusion material-infiltrated rare earth magnet precursor to produce an RTB rare earth magnet, wherein in the first step, the diffusing material is an element represented by the formula: R 2 (1-s) M 2 s (In the formula, R 2 is one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, Ce, La and Ho, and M 2 is R 2 and the rare earth element and the metal element and the inevitable impurity element which are alloyed with the rare earth element, and (1-s) and s are molar ratios, and 0.05≦s≦0.40. 14 The method comprises a main phase having a B-type crystal structure and a grain boundary phase present around the main phase, the main phase having an average grain size of 1.0 μm to 10.0 μm, and in a second step, the diffusion material-permeated rare earth magnet precursor is polished to a thickness of the surface layer less than a thickness represented by the following formula: amount of diffusion material used (amount of diffusion material relative to the total weight of the rare earth magnet precursor (weight %, wt%)) x 2.2172. Effect of the Invention
[0012] The present invention provides an RTB rare earth magnet that ensures dimensional accuracy and at the same time has excellent magnetic properties. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a diagram showing a schematic diagram of a polishing region in an example and a comparative example. [Diagram 2] 1 is a graph showing the relationship between polished area and coercive force for (A) a sintered magnet and (B) a hot-worked magnet. [Diagram 3] FIG. 2 is a schematic diagram showing the expansion of the magnet and the slotting-in of the magnet into the rotor. [Figure 4] 4 is an SEM photograph of the magnet region layer and surface layer of the unpolished portion of the magnet in Example 1. [Diagram 5] 1 is a graph showing the relationship between the amount of diffusion material used (diffusion amount) and the average thickness of the surface layer. [Figure 6] FIG. 2 is a diagram showing a schematic view of a portion of the magnets of the examples and the comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Preferred embodiments of the present invention will now be described in detail. In this specification, the features of the present invention will be described with reference to the drawings as appropriate. In the drawings, the dimensions and shapes of each part are exaggerated for clarity, and the actual dimensions and shapes are not accurately depicted. Therefore, the technical scope of the present invention is not limited to the dimensions and shapes of each part shown in these drawings. The rare earth magnet, its manufacturing method, and motor equipped with the rare earth magnet of the present invention are not limited to the following embodiments, and can be embodied in various forms with modifications and improvements that can be made by those skilled in the art, without departing from the gist of the present invention.
[0015] In the RTB rare earth magnet of the present invention, R is a rare earth element, for example, one or more selected from the group consisting of Ce, La, yttrium (Y), scandium (Sc), Nd, Pr, gadolinium (Gd), Tb, Dy, and Ho. T is an iron group element, for example, Fe, Co, or Fe and Co (Fe and / or Co), where the ratio of each element in the case of Fe and Co is not limited. B is boron. The RTB rare earth magnet of the present invention may contain one or more additive elements known in the art, for example, titanium, vanadium, copper, chromium, manganese, nickel, zirconium, niobium, molybdenum, hafnium, tantalum, tungsten, aluminum, gallium, silicon, bismuth, tin, etc., to the extent that the coercive force of the RTB rare earth magnet is not impaired.
[0016] In the RTB rare earth magnet of the present invention, the content of R is usually 10 atomic % to 20 atomic % relative to the total number of atoms in the RTB rare earth magnet. In one embodiment, the content of Nd in R is usually 8 atomic % to 20 atomic % relative to the total number of atoms in the RTB rare earth magnet. In one embodiment, the content of Pr in R is usually 1 atomic % to 10 atomic % relative to the total number of atoms in the RTB rare earth magnet. In the RTB rare earth magnet of the present invention, the content of T is 70 atomic % to 85 atomic % relative to the total number of atoms in the RTB rare earth magnet. In one embodiment, the content of Fe in T is usually 70 atomic % to 85 atomic % relative to the total number of atoms in the RTB rare earth magnet. In one embodiment, the content of Co in T is usually 1 atomic % to 10 atomic % relative to the total number of atoms in the RTB rare earth magnet. In the RTB rare earth magnet of the present invention, the B content is usually 5 atomic % to 20 atomic % relative to the total number of atoms in the RTB rare earth magnet. In the RTB rare earth magnet of the present invention, the additive element content is usually 0 atomic % to 2 atomic % relative to the total number of atoms in the RTB rare earth magnet. In one embodiment, the Ga content is usually 0 atomic % to 1.0 atomic % relative to the total number of atoms in the RTB rare earth magnet. In one embodiment, the Cu content is usually 0 atomic % to 0.5 atomic % relative to the total number of atoms in the RTB rare earth magnet. In one embodiment, the Al content is usually 0 atomic % to 0.2 atomic % relative to the total number of atoms in the RTB rare earth magnet. The content of each element in an RTB rare earth magnet may be calculated based on the amount of each element added during production, but it can also be measured by methods known in the art, such as X-ray fluorescence spectrometry (XRF), inductively coupled plasma mass spectrometry (ICP-MS), or inductively coupled plasma atomic emission spectrometry (ICP-AES).
[0017] By forming the RTB rare earth magnet from the above elements, it is possible to obtain a high coercive force.
[0018] The RTB rare earth magnet of the present invention has a magnet region layer and a surface layer.
[0019] The magnet region layer is R2T 14 A main phase having a B-type crystal structure and a grain boundary phase existing around the main phase, 14 The crystals having the B-type crystal structure are bonded to each other via the grain boundary phase. In other words, the main phase is divided by the grain boundary phase, and therefore is also magnetically divided, suppressing magnetization reversal and allowing the material to have a higher coercive force than when it is not divided by the grain boundary phase.
[0020] The average grain size of the main phase is 1.0 μm to 10.0 μm, and in one embodiment, 2 μm to 6 μm.
[0021] Here, the "average particle size" is measured as follows. A certain region is defined in a scanning electron microscope image or a transmission electron microscope image observed from a direction perpendicular to the easy axis of magnetization, and multiple lines are drawn perpendicular to the easy axis of magnetization for the main phase present in this certain region, and the diameter (length) of the main phase is calculated from the distance between the intersecting points within the main phase particle (cutting method). If the cross section of the main phase is close to a circle, it is converted to the diameter equivalent to the circle of the projected area. If the cross section of the main phase is close to a rectangle, it is converted to a rectangular approximation. The D50 value of the diameter (length) distribution (particle size distribution) obtained in this way is the average particle size.
[0022] By having the average grain size of the main phase fall within the above range, the coercive force of the rare earth magnet can be improved.
[0023] In one embodiment, the primary phase has a core and a shell surrounding the core.
[0024] The average grain size of the core portion of the main phase is usually 0.4 μm to 9.99 μm. The average thickness of the shell portion of the main phase is usually 5 nm to 300 nm. The grain size of the core portion is equivalent to the grain size of the main phase minus 2 × (thickness of the shell portion).
[0025] Here, the average thickness of the shell portion of the main phase can be measured as a compositionally modulated portion from the core portion by TEM-EDX analysis or the like.
[0026] In the main phase, the total content ratio of Ce, La, Gd, Y, and Sc in the core part to all the constituent elements of the core part is higher than the total content ratio of Ce, La, Gd, Y, and Sc in the shell part to all the constituent elements of the shell part. For example, the ratio (core part:shell part) of the total content ratio (e.g., ratio in substance amount (mol)) of Ce, La, Gd, Y, and Sc in the core part to all the constituent elements of the core part and the total content ratio (e.g., ratio in substance amount (mol)) of Ce, La, Gd, Y, and Sc in the shell part to all the constituent elements of the shell part is usually 1.1:1 to 10:1.
[0027] In the main phase, the total content ratio of Nd, Pr, Tb, Dy, and Ho in the shell portion relative to all the constituent elements of the shell portion is higher than the total content ratio of Nd, Pr, Tb, Dy, and Ho in the core portion relative to all the constituent elements of the core portion. For example, the ratio (shell portion:core portion) of the total content ratio (e.g., ratio in terms of substance amount (mol)) of Nd, Pr, Tb, Dy, and Ho in the shell portion relative to all the constituent elements of the shell portion to the total content ratio (e.g., ratio in terms of substance amount (mol)) of Nd, Pr, Tb, Dy, and Ho in the core portion relative to all the constituent elements of the core portion is usually 1.01:1 to 10:1.
[0028] The remanence and coercivity of the entire rare earth magnet can be increased by increasing the remanence and coercivity in the shell portion, rather than increasing the remanence and coercivity in the core portion. The remanence and coercivity increase as the content ratio of Nd, Pr, Tb, Dy, and Ho increases. Therefore, the diffusion and penetration of the diffusion material causes Ce, La, Gd, Y, and Sc in the rare earth magnet precursor to be discharged from the shell portion to the grain boundary phase, and Nd, Pr, Tb, Dy, and Ho in the diffusion material to be diffused and penetrated from the grain boundary phase to the shell portion, which is advantageous for improving the remanence and coercivity.
[0029] In one embodiment, the composition of the grain boundary phase is represented by the formula: R 2 (1-s) M 2 s (In the formula, R 2is one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, Ce, La and Ho, and M 2 is R 2 (1-s) and (s) are molar ratios that are 0.05≦s≦0.40. The composition of the grain boundary phase depends on the composition of the diffusion material used in the method of producing an RTB rare earth magnet, which will be described below.
[0030] The surface layer is a layer formed on the C surface of the magnet region layer.
[0031] The C-plane is a plane perpendicular to the c-axis, or easy magnetization direction, of the magnet region layer.
[0032] In the RTB rare earth magnet of the present invention, the composition of the surface layer, like the grain boundary phase, is represented by the formula: R 2 (1-s) M 2 s (In the formula, R 2 is one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, Ce, La and Ho, and M 2 is R 2 (1-s) and (s) are molar ratios that are 0.05≦s≦0.40. The composition of the surface layer depends on the composition of the diffusion material in the manufacturing method of an RTB rare earth magnet, which will be described below.
[0033] In the RTB rare earth magnet of the present invention, the average thickness of the surface layer can be adjusted by the amount of diffusion material used during production as described below, and is usually 1 μm to 50 μm, and in one embodiment, 3 μm to 30 μm. Here, the "average thickness of the surface layer" refers to the average thickness of the surface layer at the portion where the surface layer is present, where the surface layer has not been removed by polishing. The average thickness of the surface layer can be measured as the compositionally modulated portion from the magnet region layer by TEM-EDX analysis or the like.
[0034] In the RTB rare earth magnet of the present invention, the surface layer covers 85% or more, and in one embodiment 87% or more, of the total area of the C-face of the magnet region layer. The coverage rate of the C-face of the magnet region layer by the surface layer may be 100%, and in one embodiment is 99% or less, and in one embodiment is 98% or less.
[0035] In other words, in the RTB rare earth magnet of the present invention, the area of the exposed main phase on the C face of the RTB rare earth magnet, where there is no surface layer, is 15% or less of the total area of the C face of the RTB rare earth magnet, and in one embodiment, 13% or less. The area of the exposed main phase on the C face of the RTB rare earth magnet, where there is no surface layer, may be 0%, and in one embodiment, is 1% or more, and in one embodiment, is 2% or more.
[0036] In the RTB rare earth magnet of the present invention, the absence of a surface layer keeps the area of the main phase exposed on the C-face below a certain value, which results in the presence of a grain boundary phase with a high rare earth concentration around the main phase, making it possible to suppress magnetization reversal and a decrease in the coercivity of the entire magnet that would be caused by the main phase in particles with low coercivity.
[0037] The shape of the RTB rare earth magnet of the present invention is not particularly limited. The shape of the RTB rare earth magnet of the present invention can be any shape, such as a rectangular parallelepiped, a hexahedron, a flat plate, a columnar shape such as a square prism, or a cylindrical shape with a C-shaped cross section.
[0038] Furthermore, the RTB rare earth magnet of the present invention includes both magnet products in which the magnet is magnetized after processing, and magnet products in which the magnet is not magnetized.
[0039] The RTB rare earth magnet of the present invention has the above-mentioned structure and composition, which allows the RTB rare earth magnet of the present invention to have high coercivity.
[0040] The RTB rare earth magnet of the present invention can be manufactured using techniques known in the art, except for carrying out a first step of preparing a rare earth magnet precursor and a diffusion material corresponding to the composition of the surface layer and grain boundary phase so as to obtain the structure and composition of the RTB rare earth magnet of the present invention, and diffusing and penetrating the diffusion material therein during grain boundary diffusion to prepare a diffusion material-permeated rare earth magnet precursor having a magnet region layer and a surface layer covering the magnet region layer, and a second step of polishing the diffusion material-permeated rare earth magnet precursor.
[0041] The RTB rare earth magnet of the present invention can be produced, for example, as follows.
[0042] The rare earth magnet precursor for RTB rare earth magnets is first prepared by dividing a molten metal of a given composition into the main phase (R2T 14 The molten metal is cooled at a rate such that the average particle size of the rare earth magnet precursor (phase B) becomes 1.0 μm to 10.0 μm, to obtain a magnetic ribbon. Such a cooling rate is, for example, 1° C. / s to 1000° C. / s. Methods for obtaining magnetic powder at such a cooling rate include, for example, a strip casting method and a book molding method. The composition of the molten metal is basically the same as the overall composition of the rare earth magnet precursor, but for elements that may be depleted in the process of producing the rare earth magnet precursor, the amount of depletion may be taken into consideration.
[0043] The magnetic powder obtained by pulverizing the magnetic ribbon is compressed. The powder compression may be performed in a magnetic field. This allows the rare earth magnet to have anisotropy after sintering. The molding pressure during powder compression may be, for example, 50 MPa or more, 100 MPa or more, 200 MPa or more, or 300 MPa or more, and 1000 MPa or less, 800 MPa or less, or 600 MPa or less. The magnetic field applied may be 0.1 T or more, 0.5 T or more, 1 T or more, 1.5 T or more, or 2.0 T or more, and 10.0 T or less, 8.0 T or less, 6.0 T or less, or 4.0 T or less. Examples of the pulverization method include a method in which the magnetic ribbon is coarsely pulverized and then further pulverized with a jet mill or the like. Examples of the coarse pulverization method include a method using a hammer mill, a method in which the magnetic ribbon is hydrogen-embrittled, and a combination thereof.
[0044] The above-mentioned powder compact is sintered without pressure to obtain a rare earth magnet precursor. The powder compact is sintered without pressure to increase the density of the sintered compact, and sintered at high temperature for a long time. The sintering temperature may be, for example, 900°C or more, 950°C or more, or 1000°C or more, and 1100°C or less, 1050°C or less, or 1040°C or less. The sintering time may be, for example, 1 hour or more, 2 hours or more, 3 hours or more, or 4 hours or more, and 24 hours or less, 18 hours or less, 12 hours or less, or 6 hours or less. In order to suppress oxidation of the powder compact during sintering, the sintering atmosphere is preferably an inert gas atmosphere. The inert gas atmosphere includes a nitrogen gas atmosphere.
[0045] Subsequently, a diffusion material is diffused and impregnated into the rare earth magnet precursor, as described below, to produce a diffusion material-infiltrated rare earth magnet.
[0046] · First process (diffusion and penetration) The rare earth magnet precursor is impregnated with a diffusion material, which advantageously improves the coercivity of the rare earth magnet of the present invention, particularly at high temperatures.
[0047] The diffusion and infiltration of the diffusion material involves preparing a diffusion material and diffusing and infiltrating the diffusion material into the rare earth magnet precursor. The diffusion material contains, relative to the total constituent elements of the diffusion material, 60 atomic % to 95 atomic %, and in one embodiment, 65 atomic % to 80 atomic %, of one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, Ce, La, and Ho, 5 atomic % to 30 atomic %, and in one embodiment, 15 atomic % to 25 atomic %, of one or more elements selected from the group consisting of Fe and Co, and 5 atomic % to 20 atomic %, and in one embodiment, 5 atomic % to 15 atomic %, of one or more elements selected from the group consisting of fluorine, gallium, aluminum, and copper.
[0048] Methods for preparing the diffusion material include, for example, a method of obtaining a thin ribbon and / or a thin piece from a molten metal having the composition of the diffusion material using a liquid quenching method or a strip casting method, a method of casting a molten metal having the composition of the diffusion material into a mold such as a book mold, a method of loading raw materials for the diffusion material into a container, arc-melting the raw materials in the container, and cooling the molten material to obtain an ingot, and the like.
[0049] The prepared diffusion material is diffused and infiltrated into the rare earth magnet precursor. The diffusion and infiltration method typically involves bringing the diffusion material into contact with the rare earth magnet precursor to obtain a contact body, heating the contact body, and diffusing and infiltrating the molten diffusion material into the rare earth magnet precursor. The molten diffusion material diffuses and infiltrates through the grain boundary phase. The molten diffusion material then solidifies in the grain boundary phase, magnetically separating the main phases, advantageously improving the coercive force, particularly the coercive force at high temperatures.
[0050] The form of the contact body is not particularly limited as long as the rare earth magnet precursor is in contact with the diffusion material. For example, the contact body may be in a form in which the rare earth magnet precursor is in contact with a diffusion material in the form of a ribbon and / or flake obtained by a liquid quenching method and / or a strip casting method. For example, the contact body may be in a form in which the rare earth magnet precursor is in contact with a diffusion material powder obtained by pulverizing a ribbon and / or flake obtained by a liquid quenching method and / or a strip casting method, a book mold material, or an arc melting and solidifying material.
[0051] There are no particular limitations on the diffusion conditions, so long as the diffusion material diffuses into the rare earth magnet precursor, the main phase does not become coarse, and the formation of harmful phases that adversely affect magnetic properties can be suppressed.
[0052] The diffusion temperature is, for example, usually 800°C to 1000°C. The diffusion time is usually 30 minutes to 300 minutes. After the diffusion of the diffusion material, it is preferable to quickly cool the sintered body. This makes it possible to suppress the generation of harmful phases that adversely affect the magnetic property. The cooling rate is, for example, usually 10°C / min to 1000°C / min. In order to suppress oxidation of the rare earth magnet precursor during diffusion, the diffusion atmosphere is preferably an inert gas atmosphere. The inert gas atmosphere includes a nitrogen gas atmosphere.
[0053] When the diffusion material is diffused and infiltrated, 0.1 to 15.0 parts by weight, and in one embodiment 5 to 10 parts by weight, of the diffusion material is brought into contact with 100 parts by weight of the rare earth magnet precursor.
[0054] In order to diffuse the diffusion material under conditions that do not cause the main phase of the rare earth magnet precursor to become coarse, the average particle size of the main phase before and after the diffusion material is substantially in the same range of sizes. The average particle size and crystal structure of the main phase are as described above.
[0055] During the diffusion and penetration of the diffusion material, in order to suppress oxidation of the rare earth magnet precursor and the diffusion material, the diffusion and penetration atmosphere is preferably an inert gas atmosphere, including a nitrogen gas atmosphere.
[0056] · Second process (polishing) The resulting diffusion material-infiltrated rare earth magnet precursor is then polished.
[0057] The polishing of the diffusion material permeated rare earth magnet precursor is carried out so that the surface layer present on the C-side of the diffusion material permeated rare earth magnet precursor remains within 85% or more, and in one embodiment 87% or more, of the total area of the C-side of the diffusion material permeated rare earth magnet precursor. Alternatively, the polishing of the diffusion material permeated rare earth magnet precursor is carried out within an area of 15% or less, and in one embodiment 13% or less, of the total area of the C-side of the diffusion material permeated rare earth magnet precursor.
[0058] Alternatively, the polishing of the diffusion material infiltrated rare earth magnet precursor may be carried out by the method according to the following formula: Amount of diffusion material used (amount of diffusion material relative to the total weight of rare earth magnet precursor (wt%)) x 2.2172 In other words, the diffusion material is permeated so that the surface layer remains on the C surface of the rare earth magnet precursor.
[0059] By polishing the diffusion material-infiltrated rare earth magnet precursor as described above, the area of the main phase exposed on the C-face due to the absence of a surface layer is suppressed to a certain value or less, and a grain boundary phase with a high rare earth concentration is present around the main phase, making it possible to suppress magnetization reversal and a decrease in the coercivity of the entire magnet that would be caused by the main phase in particles with low coercivity.
[0060] The RTB rare earth magnet of the present invention can be included in motors known in the art. Thus, the present invention also relates to a motor including a stator core with a coil and a rotor core rotatably disposed in a hollow portion of the stator core, the rotor core including the RTB rare earth magnet of the present invention. EXAMPLES
[0061] Several examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.
[0062] 1. Grain boundary diffusion and polishing area in sintered magnets 1-1. Manufacturing of rare earth magnets Based on the above description of the method for producing a rare earth magnet, a rare earth magnet was produced as follows. First, Nd 11.3 ,Pr 2.7 , Fe balance , Co 1.1 , B 5.9 , Ga 0.4 , Al 0.2 , Cu 0.2 (The numbers are in atomic percent, and the sum of all elements is 100 atomic percent.) 20 Nd 60 Cu 20(The numbers are in atomic % and all elements added together add up to 100 atomic %) was diffused into the grain boundaries of the sintered magnet in the C-plane direction (950°C, 165 minutes) at 6% by weight of the total weight of the sintered magnet.
[0063] After the grain boundary diffusion, a part of the C-face was polished to the extent that the surface layer (residue) of the diffusion material was scraped off. The polished area was varied from 0% (no polishing) to 50% (the entire surface of one side) as shown in Figure 1.
[0064] After polishing, the magnetic properties were evaluated using a VSM. The crystal grain size (average grain size of the main phase) of the magnet was observed using a SEM.
[0065] 1-2.Results The results of the magnetic property evaluation are shown in Table 1 and Fig. 2A. In the table, "average grain size" refers to the average grain size of the main phase, and the same applies to the following tables.
[0066] [Table 1]
[0067] From Table 1 and Figure 2A, it can be seen that the coercive force drops sharply when the polished area is 20% or more. In addition, the residual magnetization also tends to decrease as the polished area becomes larger.
[0068] Therefore, to maximize the effect of improving coercivity through grain boundary diffusion, the polished area needs to be 15% or less. This is because the grain size of a sintered magnet is relatively large, and polishing the surface layer removes the particles coated with the grain boundary phase, leaving these areas with soft magnetic properties, which are thought to be the seeds of magnetization reversal. If the polished area exceeds 15%, the volume fraction of the soft magnetic property area will be high, which is thought to contribute to a decrease in the coercivity of the entire magnet.
[0069] 2. Grain boundary diffusion in sintered magnets (difference between double-sided and single-sided diffusion) 2-1. Manufacturing of rare earth magnets Based on the above description of the method for producing a rare earth magnet, a rare earth magnet was produced as follows. First, Nd 11.3 ,Pr 2.7 , Fe balance , Co 1.1 , B 5.9 , Ga 0.4 , Al 0.2 , Cu 0.2 (The numbers are in atomic percent, and the sum of all elements is 100 atomic percent.) 70 Co 20 Cu 10 (The numbers are in atomic %, and all the elements added together add up to 100 atomic %), 5% by weight of the sintered magnet's total weight was subjected to grain boundary diffusion from the C-face direction (950°C, 165 minutes). At this time, grain boundary diffusion occurred from both faces in Example 5, while grain boundary diffusion occurred from only one face in Comparative Example 5. Furthermore, in Comparative Example 6, after double-sided grain boundary diffusion, the entire C-face was polished to the extent that the surface layer (residue) of the diffusion material was scraped off.
[0070] After polishing, the magnetic properties were evaluated using a VSM. The crystal grain size (average grain size of the main phase) of the magnet was observed using a SEM.
[0071] 2-2.Results Table 2 shows the results of the magnetic property evaluation.
[0072] [Table 2]
[0073] Comparing Example 5 and Comparative Example 5 from Table 2, it was found that although the amount of grain boundary diffusion was the same, double-sided grain boundary diffusion had a higher coercivity. Also, comparing Example 5 and Comparative Example 6, it was found that when 50% of a sample with high coercivity was polished (single-sided polishing), the coercivity dropped sharply, which is consistent with the results in Table 1. Therefore, it was found that even without a polished region, grain boundary diffusion on both sides is a condition for increasing the coercivity of a magnet.
[0074] 3. Grain boundary diffusion and polishing area in hot-deformed magnets 3-1. Manufacturing of rare earth magnets Nd 13.2 , Fe balance , Co 19.8 , B 5.82 , Ga 0.3 , Al 0.05 , Cu 0.09 (The numbers are in atomic percent, and the sum of all elements is 100 atomic percent.) 80 Cu 20 (The numbers are in atomic %, and if all the elements are added together it becomes 100 atomic %), 10% by weight of the total weight of the hot-deformed magnet was subjected to grain boundary diffusion from the C-face direction (680℃, 165 minutes). After grain boundary diffusion, part of the C-face was polished to the extent that the surface layer (residue) of the diffusion material was scraped off. The polished area at this time was changed from 0% (no polishing) to 50% (entire surface of one side) as shown in Figure 1 and Table 3.
[0075] After polishing, the magnetic properties were evaluated using a VSM. The crystal grain size (average grain size of the main phase) of the magnet was observed using a TEM.
[0076] 3-2.Results Table 3 and FIG. 2B show the results of the magnetic property evaluation.
[0077] [Table 3]
[0078] From Table 3 and Figure 2B, we can see that in the case of hot-processed magnets, the coercivity is constant regardless of the polished area. Therefore, in hot-processed magnets with small grain size, the generation of low coercivity areas (soft magnetic property areas) by surface polishing is limited in volume fraction even if many areas are polished, so it is considered that this does not affect the coercivity of the entire magnet.
[0079] 4. Volume expansion rate The expansion coefficients of the magnets of Example 1 and Comparative Example 8 were measured before and after grain boundary diffusion. After grain boundary diffusion, the grain boundary phase becomes thicker, and the lattice constant of the 2-14-1 crystal structure of the shell portion changes due to the shell-forming effect of the diffusion material. For this reason, the magnet basically expands. The expansion coefficient also changes depending on the type of magnet base material, the diffusion material, and the amount of diffusion. The results are shown in Table 4.
[0080] [Table 4]
[0081] From Table 4, in Example 1, the magnet expanded by 1.2% in the ab-axis direction (in-plane direction) and 7.2% in the c-axis direction (perpendicular to the plane). On the other hand, in Comparative Example 8, the expansion rate was only 0.3% in the ab-axis direction (in-plane direction) and 11.2% in the c-axis direction (perpendicular to the plane). Therefore, by knowing the expansion rate of the magnet after grain boundary diffusion, it is possible to prepare a base magnet smaller than the expansion rate in advance and adjust the magnet dimensions after grain boundary diffusion in order to slot the magnet into the rotor, as shown in FIG. 3, for example. It was found that this allows a magnet of a predetermined size to be slotted into the rotor without generating extra voids even without polishing.
[0082] 5. Regarding grinding depth The thickness of the surface layer consisting of the diffusion material remaining on the surface was measured for the magnets in Table 1. Figure 4 shows SEM photographs of the magnet region layer and surface layer of the unpolished portion of the magnet in Example 1, and Table 5 and Figure 5 show the results.
[0083] [Table 5]
[0084] 4 and 5 show that the layer remaining on the surface tends to become thicker when a large amount of diffusion material is used, but at about 6% by weight as in Example 1, the thickness was about 13 μm. This experiment showed that the following relationship holds true: surface layer (μm) = 2.2172 × amount of diffusion material used (weight %).
[0085] Figure 6 shows a schematic diagram of the difference between the magnets in the Example and Comparative Example in this experiment. In the Example, 85% or more of the C-face of the magnet region layer of the magnet is covered with the surface layer, so high coercivity is maintained. On the other hand, in the Comparative Example, 20% or more of the C-face of the magnet region layer of the magnet is not covered with the surface layer, so the main phase is exposed, resulting in a decrease in coercivity.
Claims
1. An R-T-B rare earth magnet in which R is a rare earth element, T is Fe and / or Co, and B is boron, The R-T-B rare earth magnet has a magnet region layer and a surface layer covering a C surface of the magnet region layer, The magnet region layer is R 2 T 14 A main phase having a B-type crystal structure and a grain boundary phase present around the main phase, The average grain size of the main phase is 1.0 μm to 10.0 μm, The surface layer covers 85% or more of the C surface of the magnet region layer with respect to the total area of the C surface. The RTB rare earth magnet.
2. The R-T-B rare earth magnet according to claim 1, wherein the main phase has a core portion and a shell portion present around the core portion, and the total content ratio of Nd, Pr, Tb, Dy, and Ho in the shell portion relative to all the constituent elements of the shell portion is higher than the total content ratio of Nd, Pr, Tb, Dy, and Ho in the core portion relative to all the constituent elements of the core portion.
3. The composition of the surface layer and the grain boundary phase is represented by the formula: R 2 (1-s) M 2 s (In the formula, R 2 is one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, Ce, La and Ho, M 2 is R 2 2. The R-T-B system rare earth magnet according to claim 1, wherein s is a metal element other than rare earth elements that are alloyed with s and an unavoidable impurity element, and (1-s) and s are molar ratios, and 0.05≦s≦0.
40.
4. 2. The R-T-B rare earth magnet according to claim 1, wherein the rare earth concentration of said surface layer is higher than the rare earth concentration of said magnet region layer.
5. A motor including a stator core having a coil, and a rotor core rotatably provided in a hollow portion of the stator core, the rotor core comprising the R-T-B system rare earth magnet according to any one of claims 1 to 4.
6. A method for producing an R-T-B rare earth magnet, in which R is a rare earth element, T is Fe and / or Co, and B is boron, comprising the steps of: The method further comprising: A first step of diffusing and infiltrating a diffusion material into a rare earth magnet precursor to prepare a diffusion material-infiltrated rare earth magnet precursor having a magnet region layer and a surface layer covering a C surface of the magnet region layer; and A second step of polishing the diffusion material-infiltrated rare earth magnet precursor to produce an R-T-B rare earth magnet. Including, In a first step, the diffusing material is represented by the formula: R 2 (1-s) M 2 s (In the formula, R 2 is one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, Ce, La and Ho, M 2 is R 2 and R is a metal element other than the rare earth element and an inevitable impurity element which is alloyed with the rare earth element, and (1-s) and s are a molar ratio, and 0.05≦s≦0.
40. 2 T 14 The alloy comprises a main phase having a B-type crystal structure and a grain boundary phase present around the main phase, and the main phase has an average grain size of 1.0 μm to 10.0 μm; In a second step, a surface layer present on the C-face of the diffusion material-permeated rare earth magnet precursor is polished so that 85% or more of the total area of the C-face of the diffusion material-permeated rare earth magnet precursor remains. The method.
7. A method for producing an R-T-B rare earth magnet, in which R is a rare earth element, T is Fe and / or Co, and B is boron, comprising the steps of: The method further comprising: A first step of diffusing and infiltrating a diffusion material into a rare earth magnet precursor to prepare a diffusion material-infiltrated rare earth magnet precursor having a magnet region layer and a surface layer covering a C surface of the magnet region layer; and A second step of polishing the diffusion material-infiltrated rare earth magnet precursor to produce an R-T-B rare earth magnet. Including, In a first step, the diffusing material is represented by the formula: R 2 (1-s) M 2 s (In the formula, R 2 is one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, Ce, La and Ho, M 2 is R 2 and R is a metal element other than the rare earth element and an inevitable impurity element which is alloyed with the rare earth element, and (1-s) and s are a molar ratio, and 0.05≦s≦0.
40. 2 T 14 The alloy comprises a main phase having a B-type crystal structure and a grain boundary phase present around the main phase, and the main phase has an average grain size of 1.0 μm to 10.0 μm; In a second step, the diffusion material-infiltrated rare earth magnet precursor is polished to a thickness of the surface layer less than the thickness represented by the following formula: diffusion material usage (amount of diffusion material relative to the total weight of the rare earth magnet precursor (wt%)) x 2.2172. The method.
Citation Information
Patent Citations
Rare earth magnet and method for producing same
CN114694907A
Method for manufacturing rare earth-iron-boron based sintered magnet
JP2018082145A
Manufacturing method of rfeb type magnet
JP2019016635A
Sintered magnet and manufacturing method thereof
JP2020021804A
Rare earth sintered magnet
JP2020057734A